The use of surrogate reference standard in Quantitative HPLC: A case study of Albendazole and Quinine sulphate tablets - Obimpeh, Worlanyo James (2015)
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Philosophy (Pharmaceutical Chemistry).